Endoscopic repair of duodenal perforation with over-the-scope clipping system and endoclips: A case report - Ali Tüzün İnce and Orhan Kocaman and Kemal Yıldız and Birol Baysal and Mukaddes Tozlu and Ümit Akyüz and Ahmet Danalıoğlu and Hakan Şentürk (Turkish Journal of Gastroenterology, 2019)
Herein, we present an endoscopic repair of iatrogenic duodenal perforation by over-the-scope clipping system (OTSC) and endoclips in an 84-year-old woman that occurred during linear endosonography (EUS) examination. One OTSC and 8 clips were used for repairing the perforation hole. After 3 days in the intensive care unit (ICU) by chest tube and without oral feeding, she was discharged from the hospital at 6. admission day, and she also had an acute coronary attack during 4. hospital day. OTSC and clipping devices are very useful for repair of iatrogenic perforations, especially in older patients who have comorbid diseases and who can not tolerate the surgery. Turkish Başlık: Duodenal perforasyonun OTSC ve endokliplerle endoskopik tamiri; bir vaka takdimi Anahtar kelimeler: EUS komplikasyonları, duodenum perforasyonu, iatrojenik perforasyon, OTSC, endoskopik klip Burada lineer EUS ile inceleme sırasında duodenum perforasyonu oluşan 84 yaşında bir bayan hastanın endoskopik olarak OTSC ve kliplerle tedavisini sunuyoruz. Perforasyon deliğinin kapatılması için 1 OTSC ve 8 klip kullanıldı. Hasta göğüs tüpü takılarak ve oral beslenmesi kesilerek 3 gün yoğun bakım ünitesinde takip edildikten sonra ve 4. gününde akut koroner atak geçirmesine rağmen müracaatının 6. günü taburcu edildi. Özellikle komorbid hastalığı olan ve cerrahiyi kaldıramayacak yaşlı hastalarda OTSC ve klipler, iatrojenik perforasyonların endoskopik tedavisinde oldukça faydalıdır.